(untitled) - Gibbons, Duncan William

Qualification and certification of laser powder bed fusion for aerospace applications: a model-based production systems engineering approach. (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.